THE IMPACT OF TOURISM DEVELOPMENT ON THE ECONOMIC AND SOCIO-CULTURAL CONDITIONS OF THE COMMUNITY IN PENTINGSARI TOURISM VILLAGE : DAMPAK PENGEMBANGAN PARIWISATA TERHADAP KONDISI EKONOMI DAN SOSIAL BUDAYA MASYARAKAT DI DESA WISATA PENTINGSARI - Eginta Meliyani Br Tarigan; Carmelita Laetitia Da Costa; Chesilia Putri Greysanti; I Gede Abdi Putra Baradah (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study aims to identify and analyze the impact of tourism development on the economic and socio-cultural conditions of the community in Pentingsari Tourism Village, Yogyakarta. The research used quantitative approach with descriptive method. Data were collected through questionnaires distributed to 178 respondents consisting of the community and tourism actors. Validity and reliability tests were conducted using SPSS to ensure the accuracy and consistency of the instrument. The results showed that tourism provides significant positive impacts such as increased income, job creation, infrastructure development, and cultural preservation. Social impacts include increased community cohesion, awareness of local products, and improved communication skills. However, negative impacts also emerge such as rising prices of goods, inequality of economic benefits, changes in cultural values, and commercialization of sacred traditions. These findings emphasize the importance of a more inclusive and sustainable tourism management strategy. This research is limited to one tourism village and uses data on respondents' perceptions, which may contain bias. Further research is recommended using a mixed approach and comparative studies between regions. Keywords: tourism, economic, social and cultural impacts